Colletotrichum species associated to anthracnose in passion fruit Brazil - Jackeline Laurentino; Luiz Eduardo Monteiro Lopes; janaíne Rossane Araujo Silva-Cabral; Jaqueline Figueredo de Oliveira Costa; Gaus Silvestre de Andrade Lima; Iraildes Pereira Assunção (Universidade Estadual de Alagoas, 2022)
Brazil is the world's leading producer of passion fruit. However, among the diseases that affect the culture of passion fruit, the anthracnose, caused by species of the Colletotrichum genus causes great socioeconomic losses in northeastern Brazil. The aims of this study were to identify species of the Colletotrichum genus that infect passion fruit leaves, using multi-locus phylogenetic analysis associated to morpho-cultural characteristics, as well as to evaluate the pathogenicity in different hosts. Isolates of the Colletotrichum genus were obtained from passion fruit leaves showing typical symptoms of the disease, collected in commercial plantations in the state of Alagoas, Brazil. The pathogenic isolates were identified based on the sequence of the GAPDH, TUB2, CHS-1 genes and the ITS-rDNA region. For the cultural characterization of the identified species, the mycelial growth rate and aspect of the colonies were evaluated. In the morphological characterization the length and width of 50 conidia and appressoria were measured. The multi-locus phylogenetic analysis associated to morpho-cultural characteristics of fiftee isolates revealed five species of Colletotrichum: C. fructicola, C. theobromicola, C. plurivorum, C. brevisporum, Colletotrichum sp. This is the first report of C. fructicola and C. theobromicola in the world and of C. brevisporum and C. plurivorumin Brazil. The Colletotrichum species were pathogenic to different inoculated hosts (mango, passion fruit, banana, papaya and guava), with the exception of the C. brevisporum, Colletotrichum sp. and C. plurivorum to guava fruit.